Catalytic Applications of Pyridine‐Containing Macrocyclic Complexes. Issue 30 (20th July 2017) - Tseberlidis, Giorgio; Intrieri, Daniela; Caselli, Alessandro
Abstract : The introduction of a pyridine moiety into the skeleton of a polyazamacrocyclic ligand affects both the thermodynamic properties and the coordination kinetics of the resulting metal complexes. These features have attracted great interest from the scientific community in recent years. The field of application of pyridine‐containing macrocyclic ligands ranges from biology to supramolecular chemistry, encompassing MRI, molecular recognition, materials and catalysis. In this microreview we provide a perspective of the catalytic applications of metal complexes of pyridine‐containing macrocycles, including an account of investigations from the authors' laboratories dealing with stereoselective C–C and C–O bond‐forming reactions. The increased conformational rigidity imposed by the pyridine ring allowed for the isolation and characterisation of metal complexes in high oxidation states and the study of their relevance in oxidation reactions. On the other hand, the very different conformations accessible upon the metal coordination and the easily tuneable synthesis of the macrocyclic ligands have been exploited in stereoselective synthesis. Abstract : In this microreview we provide a perspective on the catalytic applications of metal complexes of pyridine‐containing macrocycles, with a focus of interest on the structural features imposed on the metal complexes by the presence of the pyridyl moiety.